An Explanation for Reports of Increased Prevalence of Olfactory Dysfunction With Omicron: Asymptomatic Infections - von Bartheld, Christopher S; Wang, Lingchen (The Journal of infectious diseases, 2024)
Abstract The prevalence of olfactory dysfunction (OD) in people infected with the Omicron variant is substantially reduced compared with previous variants. However, 4 recent studies reported a greatly increased prevalence of OD with Omicron. We provide a likely explanation for these outlier studies and reveal a major methodological flaw. When the proportion of asymptomatic infections is large, studies on the prevalence of OD will examine and report predominantly on nonrepresentative cohorts, those with symptomatic subjects, thereby artificially inflating the prevalence of OD by up to 10-fold. Estimation of the true OD prevalence requires representative cohorts that include relevant fractions of asymptomatic cases. Olfactory dysfunction is thought to be much less frequent with Omicron than it was with previous variants, yet a few outlier studies concluded the opposite. The discrepant reports appear to be due to a methodological flaw: examination of nonrepresentative cohorts.